Therapeutic Exercise for Lower Back Pain Reduction and Posture Improvement In Elementary School Students - Diyah Proboyekti; Aisyah Lifsantin Na’ima (Universitas STRADA Indonesia, 2020)
The research method used was pre-experimental research which was conducted on elementary school students without using a control group. This research was conducted online at SDN Sonorejo 2 Kediri in August 2020. Pain measurement used the Wong-Baker Faces Pain, which was measured at the pretest and posttest. The results showed that the mean pretest score was 4.07 and for the post-test average score was 0.87. This shows that the mean pretest score results are in the interpretation of a little more pain, while the average posttest score results are in the painless interpretation, which means that there is a decrease from the average pretest score results. Wilcoxon test results obtained p value = 0.000 where α = 0.05, so it can be concluded that there is a significant reduction in low back pain after giving therapeutic exercise